Elucidating the resistance mechanisms and binding pattern of novel Oxa-48-like carbapenemases covalent inhibitors: A hybrid experimental and in silico approach - Sehra, Gul e; Azam, Sadiq; Ahmad, Sajjad; Ali, Amjad; Khan, Ibrar; Ullah, Asad; Waqas, Muhammad; Rehman, Noor; Absar, Muhammad; Alshammari, Abdulrahman; Albekairi, Norah A.; Wei, Dong-Qing (Journal of molecular structure, 2025)
•The isolates were resistant to SXT, AMP, FEP CTX, CIP, TET, MEM, and IPM, while effective antibiotics were TGC, FOS, FOX, SCF and TZP.•The sequencing and mutational analysis of the OXA-48 gene revealed 45-point mutations.•Five novel missense mutations (Thr104:Ala104, Asn110:Asp110, Glu168:Gln168, Ser171:Ala171 and Arg214:Ser214).•These mutations can contribute to the antibiotic affinity decrease and cause resistance.•10 compounds (ZINC103533306, ZINC103531564, ZINC3861001, ZINC103533375, ZINC12411532, ZINC103533290, ZINC12376465, ZINC85875819, ZINC59586513 and ZINC13370550) showed best fit and high interactions with the OXA-48 active pocket. Klebsiella pneumoniae is a Gram negative bacteria that can cause harm to the public's health and vulnerability has increased due to the emergence of highly virulent strains resistant to carbapenem antibiotics. The K. pneumoniae resistance mechanism involves extended-spectrum beta-lactamases, which are enzymes that can break down a broad range of antibiotics. The particular concern is Class D β-lactamases like OXA-48, which further complicates treatment options for infections caused by K. pneumoniae. The current study screened 7800 samples from three hospitals in Pakistan and found 353 positive samples of K. pneumoniae. The isolates were resistant to SXT, AMP, FEP CTX, CIP, TET, MEM, and IPM, while effective antibiotics were TGC, FOS, FOX, SCF and TZP. The sequencing and mutational analysis of the OXA-48 gene revealed 45-point mutations, including five novel missense mutations (Thr104:Ala104, Asn110:Asp110, Glu168:Gln168, Ser171:Ala171 and Arg214:Ser214). These mutations can contribute to the antibiotic affinity decrease and cause resistance. Furthermore, the study aimed to develop covalent inhibitors of OXA-48 (wild type and mutant) carbapenemases using a combination of molecular docking and molecular dynamic (MD) simulation approaches from natural products from the ZNINC20 database. 10 compounds (ZINC103533306, ZINC103531564, ZINC3861001, ZINC103533375, ZINC12411532, ZINC103533290, ZINC12376465, ZINC85875819, ZINC59586513 and ZINC13370550) showed best fit and high interactions with the OXA-48 active pocket. The binding free energies calculated from the MD showed that these compounds have high affinity with both the wild type and mutated OXA-48 protein. The selected compounds showed good drug-like properties and can be the leading inhibitors to combat the resistant K. pneumoniae strains.